Soil physic properties related to forage offer levels of dwarf elephant grass cv. Mott - Bertol, Ildegardis; Almeida, Jaime Antonio de; Almeida, Edison Xavier de; Kurtz, Claudinei (Pesquisa Agropecuaria Brasileira, 2000)
Animal grazing at different grazing pressures can affect some important soil properties on pastures, increasing soil susceptibility to water erosion and decreasing its productive capacity. The experiment was conducted at EPAGRI Experimental Station, in 1996, Ituporanga, Santa Catarina State, Brazil, with the objectives of evaluating alterations in soil density, porosity, weighed average diameter of aggregates and soil water infiltration rate on dwarf elephant grass (Pennisetum purpureum Schum.) cv. Mott pasture submitted to different forage offer levels. The levels of forage on offer were: 4.0, 8.0, 12.0 and 16.0%, besides a natural pasture treatment without grazing and a native forest area (checkplot), on sandy loam soil (Inceptisol). The results showed a decrease on porosity and weighed average diameter of aggregates for treatments with lower forage on offer. Soil water infiltration rate increased in the lower levels of forage on offer. Below the critical level of forage on offer of 12.0%, soil physical properties were strongly affected by the higher grazing pressure levels.